Effects of two doses of glucose and a caffeine–glucose combination on cognitive performance and mood during multi‐tasking. (28th July 2014) - Scholey, Andrew; Savage, Karen; O'Neill, Barry V.; Owen, Lauren; Stough, Con; Priestley, Caroline; Wetherell, Mark
<x xml:space="preserve">Abstract</x> Background This study assessed the effects of two doses of glucose and a caffeine–glucose combination on mood and performance of an ecologically valid, computerised multi‐tasking platform. Materials and methods Following a double‐blind, placebo‐controlled, randomised, parallel‐groups design, 150 healthy adults (mean age 34.78 years) consumed drinks containing placebo, 25 g glucose, 60 g glucose or 60 g glucose with 40 mg caffeine. They completed a multi‐tasking framework at baseline and then 30 min following drink consumption with mood assessments immediately before and after the multi‐tasking framework. Blood glucose and salivary caffeine were co‐monitored. Results The caffeine–glucose group had significantly better total multi‐tasking scores than the placebo or 60 g glucose groups and were significantly faster at mental arithmetic tasks than either glucose drink group. There were no significant treatment effects on mood. Caffeine and glucose levels confirmed compliance with overnight abstinence/fasting, respectively, and followed the predicted post‐drink patterns. Conclusion These data suggest that co‐administration of glucose and caffeine allows greater allocation of attentional resources than placebo or glucose alone. At present, we cannot rule out the possibility that the effects are due to caffeine alone Future studies should aim at disentangling caffeine and glucose effects. © 2014 The Authors. Human Psychopharmacology: Clinical and Experimental published by John Wiley & Sons, Ltd.